2019
DOI: 10.1016/j.physletb.2019.134994
|View full text |Cite
|
Sign up to set email alerts
|

Short-distance constraints for the HLbL contribution to the muon anomalous magnetic moment

Abstract: The hadronic light-by-light contribution to the muon anomalous magnetic moment depends on an integration over three off-shell momenta squared (Q 2 i) of the correlator of four electromagnetic currents and the fourth leg at zero momentum. We derive the short-distance expansion of this correlator in the limit where all three Q 2 i are large and in the Euclidean domain in QCD. This is done via a systematic operator product expansion (OPE) in a background field which we construct. The leading order term in the exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
172
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 306 publications
(182 citation statements)
references
References 68 publications
8
172
0
2
Order By: Relevance
“…In the future, the matching to pQCD could be improved if explicit calculations of pQCD corrections became available, a first step in this direction was already taken in ref. [61]. Moreover, the phenomenological analysis would profit from further experimental information on the two-photon physics of hadronic resonances in the 1-2 GeV region, which holds true not only for the longitudinal amplitudes but in general.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the future, the matching to pQCD could be improved if explicit calculations of pQCD corrections became available, a first step in this direction was already taken in ref. [61]. Moreover, the phenomenological analysis would profit from further experimental information on the two-photon physics of hadronic resonances in the 1-2 GeV region, which holds true not only for the longitudinal amplitudes but in general.…”
Section: Discussionmentioning
confidence: 99%
“…In close analogy to HVP, where perturbative QCD (pQCD) becomes applicable in the high-energy tail of the dispersive integral, such constraints arise from the OPE and pQCD. In the regime where all three virtualities are large it was shown recently [61] that the pQCD quark loop indeed arises as the first term in a controlled OPE, with the next order suppressed by small quark masses and condensates. For the case in which one virtuality remains small, the leading OPE constraint was derived in ref.…”
Section: Contentsmentioning
confidence: 95%
See 1 more Smart Citation
“…In the limit where all Q 2 i are large, the calculation from [43] establishes the pQCD quark loop as the first term in a systematic OPE. In particular, this implies the constraint…”
Section: Ope Constraints On Hlbl Scatteringmentioning
confidence: 99%
“…Recently, it was shown that the former situation can be addressed in a systematic operator product expansion (OPE), in which the pQCD quark loop emerges as the first term in the expansion [43]. The second configuration is related to so-called mixed regions in the g − 2 integral, i.e., integration regions in which asymptotic arguments only apply to a subset of arXiv:1910.11881v1 [hep-ph] 25 Oct 2019 the kinematic variables, while hadronic physics may still be relevant for others.…”
Section: Introductionmentioning
confidence: 99%